Legal Standing of Spouse Consent in Sale and Purchase Agreement of Shares from Perspective of Separation of Company’s Assets to Create Legal Certainty in Investment in Limited Liability - Hutomo, Putra (Faculty of Law, Universitas Pekalongan, 2024)
In a limited liability company, which is a limited legal organization with liability limited to paid-up capital, shares are defined as proof of a legal subject's participation in capital ownership. Shares can be bequeathed, pledged, transferred, gifted, and kept in trust. A limited liability business can be invested in, for example, by buying and selling shares. Therefore, by taking into consideration joint assets, inherited assets, or marriage agreements, it is required to include the spouse's permission in the transfer of rights in order to offer legal certainty regarding the presence of assets' separation in a limited liability business